Soil-transmitted helminthiasis among school-aged children in Myanmar: the result of 14 years after the implementation of deworming - Oo, Soe Min; Tun, Aung; Htoon, Thi Thi; Kyaw, Phyo Phyo; Htut, Win Lae; Lin, Maung Maung (International Journal Of Community Medicine And Public Health, 2020)
Background: Soil-transmitted helminth (STH) infections were the most common infections among school-aged children (SAC) in Myanmar. The routine school-based mass drug administration (MDA) with twice a year frequency has started in 2005. Methods: This cross-sectional study aimed to determine the prevalence and intensity of STH infection among SAC as the follow-up study after 14 years of MDA. In August 2019, 1000 school-aged children attending Grades 4 and 5 from four geographical regions across the country were enrolled using a multi-stage sample random sampling. The anthropometry and hemoglobin concentration was measured, and stool specimens were detected parasite eggs using the Kato Katz technique. Results: The intensity of infection was classified according to WHO criteria. Infection prevalence was 17% for any STH infections, 10.4% for A. lumbricoides, 17% for T. trichiura, and 2% for the hookworm. All STH infections were virtually not detected in the hilly region. The highest prevalence of A. lumbricoides and T. trichiura infection were seen in the coastal region. The hookworm was seen only in the plain region. The underweight prevalence was 9% and anemia prevalence was 38% while there were huge differences across regions. The finding showed that STH infections continued to be endemic among SAC throughout the country except for the hilly region after 14 years of MDA. Conclusions: The regular deworming program should be reduced to once a year frequency in Myanmar. Triple-dose regimens should be considered to eliminate the whipworms. The burden of anemia among SAC should also be addressed in cooperation with MDA.